PENGARUH PENGUASAAN TATA BAHASA BAHASA JEPANG TERHADAP KEMAMPUAN MENULIS KARANGAN MAHASISWA ANGKATAN 2020 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Monalisa Monalisa; Nana Rahayu; Hadriana Hadriana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research contains about the influence of mastery of grammar on the ability to write essays. The problem that will be discussed in this study is the effect of mastery of grammar on the ability to write essays. The purpose of this research is to explain the influence of mastery of grammar on the ability to write essays. The method used in this study is a quantitative descriptive method. The samples used in this study were 2020 Batch students, totaling 27 people and the data obtained were 20 students.Data analysis techniques are described using descriptive statistical analysis, correlation analysisProduct Moment Pearson and simple linear regression analysis to answer the problems and hypotheses. Furthermore, the data will be analyzed using correlation using the help of the programIBM SPSS 24.0.Keywords: Influence, Grammar, Essay Writing